Efektivitas dan kontribusi tindakan penagihan pajak terhadap penerimaan pajak di KPP Malang Utara - Maria Faustina Kepa; Dewi Kusumowati (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2021)
This study aims to determine how much the effectiveness and contribution of collection actions using letters of reprimand and coercion on tax revenues at KPP Pratama Malang Utara. The type of data in this study is quantitative. Source of data in the form of secondary data. This study uses quantitative descriptive analysis techniques. The results showed that tax collection with warning letters in 2018 and 2019 was declared ineffective and tax collection with forced letters in 2018 and 2019 was declared less effective, while the contribution of collection with warning letters and forced letters to tax receipts was very less. This is due to the Tax Insurer who has changed his home address but did not report it, the Tax Insurer is unable to pay off his tax debt, the lack of awareness of the Tax Insurer and the Tax Insurer does not recognize the tax debt.